Peran Bhabinkamtibmas Dalam Kegiatan Sambang Untuk Menekan Jumlah Kenakalan Remaja - Bibin, Moch Thilio Bintang Onasis (Police Studies Review, 2020)
Juvenile delinquency that occurs around the Purwakarta City Police Station jurisdiction is very unsettling to local residents. In addition, this juvenile delinquency has infected various social elements, it also makes the future of a teenager become a little constrained. This juvenile delinquency is usually done by unscrupulous elements. The researcher used several theories and concepts such as communication theory, management theory, Community Police Officers (Bhabinkamtibmas) concept, sambang concept, and role concept. By using a qualitative approach with a descriptive analysis design, this method was used in order to obtain the broadest picture of the problem that occurs. Qualitative approach provides descriptive data in the form of words orally delivered by the primary source during an interview. Therefore, an in-depth exploration of the problem can be carried out. The results of the study found that: (1) the development of juvenile delinquency had infected all elements of adolescents; (2) the role and the function of Community Police Officers (Bhabinkamtibmas) to prevent the rise of juvenile delinquency is still participatory and less functioning; (3) The influencing factors are found out to be internal and external. Internal factors such as human resources, budget, facilities, and infrastructure and leadership policies. External factors such as community participation, cooperation, and social communication. From the results of the study, the researcher provides a suggestion to Community Police Officers (Bhabinkamtibmas) to use the sambang system because it is considered to be more effective to enter the families of the perpetrators. In addition, the researcher suggests that the head of the district police to add more Community Police Officers (Bhabinkamtibmas) personnel in the Purwakarta city Police Station, to take a part in the vocational education of Community Police Officer (Bhabinkamtibmas), to provide a two wheeled vehicles such as motorcycle, and to consider the leader's policy.